Simulation of suction caisson foundations under uplift load considering strain softening and rate effect of clay - DAI Jialin; ZHANG Wei; LUO Lunbo; LI Zhou; YU Guangming (Shenzhen Daxue xuebao. Ligong ban)
It is of great significance to study the uplift bearing characteristics of suction caisson foundations for the safe service performance of offshore tension leg platform (TLP) and multi-leg wind turbine. Based on the secondary development of ABAQUS, a numerical model of suction caisson foundations considering strain softening and rate effect of soft clay is established. The numerical results are compared with the theoretical and experimental results to verify the reliability of the numerical model. The simulation results show that the change of soft clay strain softening parameters has less than five percent influence on the peak of uplift load, while the rate effect has obvious influence on the peak of uplift load and the difference caused by the change of rate effect parameters is more than forty percent. The peak of uplift load increases linearly withthe caisson outer wall roughness, and the effect of strain softening and rate effect on the uplift load caused by the caisson outer wall roughness can be ignored. For the caisson groups foundation, the caisson group effect becomes obvious with the decrease of caisson spacing, and the bearing capacity can be reduced by up to ten percent. When the caissons spacing is more than one and a half times of the caisson diameter, the caisson groups effect can be ignored.